The Urgency of Motivation to Seek Knowledge (Analysis of the Prophet's Hadiths About Education) - Robitul Abror; Ahmad Mohammad Tidjani (Penerbit Hellow Pustaka, 2024)
Motivation plays an important role in seeking knowledge in Islam. This study examines the concept of motivation in Islamic teachings, especially in educational contexts, through the analysis of relevant hadiths. In Islamic teachings, motivation is referred to as